Pengaruh Net Profit Margin (NPM), Return On Asset (ROA), Earning Per Share (EPS), dan Debt to Equity Ratio (DER) terhadap return saham sektor consumer goods industry pada Bursa Efek Indonesia periode 2017-2021 - Indriawati, Ella; Hidayati, Amalia Nuril; Fuadilah Habib, Muhammad Alhada (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The rapid development of technology is now attracting the attention of potential investors to invest in the capital market. The expectation of investors in investing is to obtain a high level of profit regardless of the risks involved. The purpose of this study was to examine the effect of net profit margin (NPM), return on assets (ROA), earnings per share (EPS)and to equity ratio (DER). on returns stock consumer goods industry listed on the IDX in 2017-2021. The population in this study amounted to 74 companies registered in the consumer goods industry, with a total sample of 8 companies through purposive sampling technique. The use of data is taken from secondary data, namely annual report that has been published. This research method uses a quantitative approach while the type of research is associative. Based on the research conducted using the t test, it was found that all variables had a significant effect except the DER variable. While the f test shows that all variables NPM, ROA, EPS, and DER have a significant effect on the Returns.